Optical properties of two-dimensional semi-conductive MXene Sc₂COₓ produced by sputtering - Chen, Qiran (2021)
Semi-conductive MXene Sc₂COₓ is synthesized by using magnetron sputtering. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) is performed to determine the composition of sample. The bandgap of Sc₂COₓ sample is determined by ultraviolet-visible (UV–VIS) range absorption and photoluminescence (PL) spectrum. The Tauc plot indicates that Sc₂COₓ is a direct bandgap material. The high sensitivity of scandium to oxygen makes the sample contain both scandium carbide and scandium oxide. Thermal annealing introduces more oxidation into the sample. Structure of MXene will be broken when the annealing temperature is higher than 600 °C.